A MODEL OF MIXED STRATEGIC ORIENTATIONS BASED ON ENVIRONMENT IN ACHIEVING ATOUGH PERFORMANCE OF SMEs - Darmanto Darmanto; Budiyono Budiyono; Sri Wardaya; Lilis Setyarini; Basuki Sri Rahayu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
Abstract: This study aims to design a model in achieving superior performance of MSMEs. The mixed strategic orientations of demography, economy and cultural values are used to design this model. The population of this study consists offood MSMEs in Central Java. The 750 samples are chosen with convenient sampling technique. Data analysis method used the Crosstab Analysis and Structural Equation Model (SEM). The result of this research is a model explaining that demography, economy and cultural values influence antecedent variables of customer orientation, dimension of strategic orientations and organizational performance. The antecedent variables affect customer orientation; the dimension of strategic orientations affects performance; Variable of change of capacity unmoderated customer and competitor orientations on innovation orientation. Variable of competitive advantage unmediated customerand competitor orientations on performance. Keywords: Mixed strategic orientations, Demography, Economy, Cultural values, Performance